ANTIBIOTIC PROPHYLAXIS WITH DIFFERENT ANTIBIOTIC REGIMEN IN PROSTATE BIOPSY PATIENTS - Wibisono, Dimas Sindhu; Soebadi, Doddy M.; Soetojo, Soetojo; Budiono, Budiono (Indonesian Journal of Urology, 2013)
Objective: To know the incidence of urinary tract infection (UTI) with different antibiotic prophylaxis for transrectal ultrasonography (TRUS) prostate biopsy. Material & Method: The study included 34 patients at Soetomo Hospital Surabaya, who were divided into 2 groups, each group consisting of 17 patients. In the first group patients received 1000 mg of ciprofloxacin orally, in the second group cefotaxime 1000 mg iv was given prior to biopsy. The two groups were compared in terms of UTI incidence as observed from the blood levels of leukocytes, C-reactive protein (CRP) and urine culture 3 days after the procedure. Results: Based on blood leukocyte levels, there was no statistically significant difference between the two groups (p = 0,74 and p = 0,42). So was the comparison of CRP levels. There was no other significant difference found (p = 0,53 and p = 0,27). From the results of urine culture, the ciprofloxacin group had positive urine culture results lower than the cefotaxime group (29,4% : 35,3%), although it was not statistically significant (p = 1,0). Conclusion: Based on the parameters of blood leukocytes levels, CRP and urine culture, there were no differences in the incidence of UTI after biopsy in the two groups.Keywords: TRUS prostate biopsy, UTI, ciprofloxacin, cefotaxime.